Coacervates derived from mussel foot proteins - Guo, Qi (Nanyang Technological University, 2022)
Biomimetics has inspired the development of various advanced technologies and novel materials, in which mussel adhesion has been regarded as a practical strategy to investigate the underwater adhesives with robust wet adhesion capacities attributed to the abundant post-translationally modified amino acid l-3,4-dihydroxyphenylalanine (Dopa) in mussel foot proteins (Mfps). Moreover, recent studies also reveal that the secretion of Mfps is conducted with a concentrated fluidic phase regulated by a liquid-liquid phase separation (LLPS) process. With the aim of exploring the phase behaviors of mussel plaque proteins and their Dopa-involved mechanisms, two mussel plaque proteins of different mussel species were chosen to gain insight into the natural secretion process and to have a deep understanding of the interaction information to the molecular level.